IMPLEMENTASI PROGRAM SMK PUSAT KEUNGGULAN (SMK PK) MELALUI DUNIA INDUSTRI DAN DUNIA KERJA (IDUKA) DI SMK NEGERI PERTANIAN PEMBANGUNAN CIANJUR - Iriantara, Yosal; Yoseptry, Ricky; Ma’mur, Ali; Dariah, Dinar; Nurani, Sani; Prasetiawati, Eka; Jamilah, Nina (STKIP PGRI Situbondo, 2025)
The SMK Centre of Excellence program present aims to produce competent and highlighted graduates by the working world of its competent graduates can be superior to its discretion. This study is a qualitative approach. A qualitative approach is a research method that describes the object of research by the obtained in the field to obtain maximum results, this study uses data collection techniques of observation, interviews, and documentation as a reference to obtain the desired results. The result of this research is (1)SMKN PP Cianjurimplement eight vocational programs excellence centers by cooperating with IDUKI, speakers from the branch of education department of Region VI, University of Bandung, and BMTI as the companion of vocational center of excellence. As well as using methods adapted to the type of activity. (2) partners who cooperate with SMKN PP Cianjur CV. Dejee fish, PT Suritani Pemuka, BBPBAT Sukabumi, BBPPMPV Cianjur, Pt. Aquatech Indo, Jd Grosir, Poktan Titipan Ilahi, Poktan Tani Makmur The form of cooperation between schools and partners such as link and match cooperation, teacher training, implementation of competency test, and absorption of graduation. (3)the impact of the vocational program center of excellence is the increasing number of teachers who have certificates, of Competence, Improve the facilities and infrastructure of IDUKA standards, can use the digital platform, and can increase partnership with IDUKA.